Problematika Orang Tua Dalam Penanaman Ibadah Pada Anak Di Kota Medan - Zachra Fahira; Abdul Fattah Nasution (UIN Sultan Maulana Hasanudin Banten, 2024)
This study aims to determine the Problems of Parents in Instilling Children’s Worship Education in Kampung Baru Village, Medan Maimun District and how efforts to overcome these problems. The method used is descriptive qualitative method with the type of research that is field research or field research. Data collection is done by conducting interviews with parents in Kampung Baru Village, Medan Maimun Subdistrict as the primary data source then observation is done by observing how parents instill worship education to children, by seeing the application of worship education carried out by children. Data analysis techniques are carried out by data reduction, data presentation, and conclusion drawing or verification. The results showed that the problems faced by parents are the lack of time owned by parents to instill children’s worship education, as well as the lack of knowledge and awareness of parents in instilling children’s worship education in Kampung Baru Village, Medan Maimun District. The contribution of this research is to provide advice to parents and children how important it is to instill worship education to children, namely by telling the importance of prayer, reading the Qur’an and fasting in the month of Ramadan.